Optimization of Preparation of Foamed Concrete Based on Orthogonal Experiment and Range Analysis - Cong, Menglong; Zhang, Shanshan; Sun, Dandan; Zhou, Kunpeng (Frontiers in Materials, 2021)
For the purpose of reducing the energy consumption and construction cost of buildings, the preparation process of geopolymer based foamed concrete, which is a novel material of the wall and roof of building, had been studied in detail. Water glass and sodium hydroxide were used as the alkali activator to excite the mixture consists of slag, fly ash and Kaolin to form the geopolymer matrix, and finally the foams generated using the physical foaming method were filled into the geopolymer matrix to produce geopolymer-based foamed concrete blocks. In the preparation process, firstly one of the four parameters of foam content, water-binder ratio, water glass content, and water glass modulus had been changed separately to study the influence of a single factor on the compressive strength, dry density, thermal conductivity and specific strength of foamed concrete blocks. The experimental results show that the above four factors have different degrees of influence on the concerned performances. Next, some representative combinations of these factors were constructed by orthogonal experiment method, and the influence degree of each combination on the concerned performances was determined by means of range analysis. According to the results of analysis, the most important influencing factor in terms of thermal conductivity was the water-binder ratio, followed by foam content, water glass modulus and water glass content. When the foam content is 1.58%, the water-binder ratio is 0.45, the water glass content is 30%, and the water glass modulus is 1.2, the thermal conductivity of the prepared geopolymer foam concrete reaches 0.044 W/(m∙K), which satisfies the expected requirements for heating in severe cold areas.